Prenatal Marihuana, Cigarettes, Alcohol and Attentional Behavior - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
A follow-up study of intentional behavior in 6 year old children exposed prenatally to marihuana, cigarettes and alcohol is reported from the Department of Psychology, Carleton University, Ottawa, Ontario, Canada.